(untitled) (Nepalese Veterinary Journal, 2018)
Toxoplasmosis is a cosmopolitan parasitic zoonosis, infecting human and other warm-blooded animals worldwide. This disease has economic importance in regard to animal reproduction, and it leads to abortions and neonatal complications in humans. This study was carried out to determine the seroprevalence of Toxoplasma gondii in sheep, cattle, cats and human in Inaruwa and surrounding areas of Sunsari district, Nepal. Altogether 336 blood samples, of which 50 from sheep, 92 from cattle, 44 from cats and 150 from human were collected and tested immediately using lateral fl ow chromatographic immunoassay (Toxo IgG/IgM Combo Rapid test®). Associated biometric information such as age, sex, pregnancy status, occupation, association with cat was recorded and analyzed to determine the association of risk factors with the disease. Data were analyzed using R 3.2.2 (The R foundation for Statistical Computing, 2015). Seroprevalence of toxoplasmosis was detected 12.00% (95% CI: 4.53- 24.31%) in sheep, 8.70% (95% CI: 3.83- 16.42%) in cattle, 36.36% (95%CI: 22.41- 52.23%) in cats and 12.67% (95% CI: 7.80- 19.07%) in human. In case of human, 31 to 45 years age group were found more susceptible to toxoplasmosis (21.74%, OR: 6.4) in comparison to 21 to 30 years (10.0%) and up to 20 years (4.17%) age groups. Toxoplasmosis was found highly significantly associated with abortion (58.33%, OR= 15.4, P=0.0001) in human in the tested individuals. Regarding occupation, 20.83% butchers were seropositive followed by farmers (15.52%), housewives (10.0%) and diagnostic lab technicians (8.0%). Female and higher age group showed high prevalence of toxoplasmosis in all studied species. Therefore, this assay is a useful method for the serological screening of toxoplasmosis in different animals and humans.